2020
DOI: 10.1093/ijnp/pyaa075
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Amnesic and Neuroprotective Effects of Fluoroethylnormemantine in a Pharmacological Mouse Model of Alzheimer’s Disease

Abstract: Background Current therapies in Alzheimer's disease (AD), including Memantine, have proven to be only symptomatic but not curative nor disease-modifying. Fluoroethylnormemantine (FENM) is a structural analogue of Memantine, functionalized with a fluorine group that allowed its use as a positron emission tomography tracer. We here analyzed FENM neuroprotective potential in a pharmacological model of AD, in comparison to Memantine. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Compound 10b attenuated the deficit at both 0.1 and 0.3 mg/kg, significantly at the lowest dose tested, but was not active at 1 mg/kg (Figure B). These bell-shaped dose–response effects are commonly observed in cognitive and neuroprotection responses in vivo , as shown recently with the NMDAR antagonist memantine in the same Aß 25–35 mouse model of AD . They are here observed in our study for both ACY1215 and 10b at the 1 mg/kg dose, suggesting that this biphasic effect relies on HDAC6 inhibition.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Compound 10b attenuated the deficit at both 0.1 and 0.3 mg/kg, significantly at the lowest dose tested, but was not active at 1 mg/kg (Figure B). These bell-shaped dose–response effects are commonly observed in cognitive and neuroprotection responses in vivo , as shown recently with the NMDAR antagonist memantine in the same Aß 25–35 mouse model of AD . They are here observed in our study for both ACY1215 and 10b at the 1 mg/kg dose, suggesting that this biphasic effect relies on HDAC6 inhibition.…”
Section: Resultssupporting
confidence: 89%
“…Nonspatial long-term memory was analyzed using the step-through passive avoidance response, with training on day 9 and retention on day 10. In this administration scheme, not symptomatic effects, but neuroprotectivity can be assessed in vivo . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that FENM may alter the recall of fear memory traces, ultimately leading to a rapid and long-lasting attenuation of behavioral fear responses. Moreover, FENM was recently shown to improve spatial learning and object recognition as well as reduce spatiotemporal disorientation in a rodent model of AD, suggesting that the results we observed during cued FC were specific to fear expression ( Couly et al, 2020 ). Future studies will be necessary to test whether FENM can alter fear memory traces to attenuate learned fear.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, because both compounds bind to phencyclidine sites in the NMDAR channel pore, these data suggest that the compounds may also exert similar behavioral effects. However, while the antidepressant-like effects of FENM remain unknown, recent data indicate that FENM enhances cognitive function and exerts neuroprotective properties in a mouse model of AD ( Couly et al, 2020 ). In this study, Couly and colleagues found that FENM reversed deficits in long-term memory, navigation, and place learning, and object recognition in a pharmacological model of AD.…”
Section: Introductionmentioning
confidence: 99%